Knowledge of the territory in solidarity economy: Learnings for an endogenous development of buen vivir (good living) - Alvarez, Claudia (Cooperativismo & Desarrollo, 2017)
Purpose: This article proposes a reflection about the existence of ancestral knowledge in the territories of the solidarity economy, or of other economies, as part of the endogenous development. Description: The reflection is born of the research carried out by the author in her doctoral thesis and her works in university formation, extension and investigation about social and solidarity economy. It is aimed at researchers, in general, and at educators of the social and solidarity economy, in particular. Point of view: The incorporation of experiences in everyday life –at all levels and college careers, undergraduate and postgraduate degrees– related to the social and solidarity economy, is an indispensable condition for endogenous development, since it is not possible to transform that which remains unknown. Conclusions: the knowledge of the territory in solidarity economy requires new learnings in forums spaces, which allow social and collective construction of new epistemologies of knowledge that, instead of reproducing hegemony and monocultural attitudes, foster a joint growth of processes of co-construction of mutual-benefit knowledge.